Territoriality of Law and the International Trade Game: Towards a New Institutional Economics of International Transactions - Hans-Jörg Schmidt-Trenz; Dieter Schmidtchen (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2006)
The conventional theory of international trade is dominated by a model presupposing a legal order that is perfect in its specifications and controllability, binding for all economic agents, no matter their nationality. World order appears to be cosmopolitan in the sense of Kant. An international private law community such as this, however, does not exist. In fact, there is a multitude of legal orders and a territoriality of law, leading to problems largely neglected in the traditional theory of international trade. They are at the heart of what we would like to call the New Institutional Economics of International Transactions (NIEIT) – a research program which started from a monograph published in 1990 (see Schmidt-Trenz 1990). This paper addresses two questions: Which specific problems emerge in contracts and the contracting process because of factors such as the multitude of legal orders and the territoriality of law? What solutions are there to these problems a) on the level of the law, and b) in the shadow of the law or completely independent of it (?private ordering?)? How do they work from an efficiency point of view? We restrict attention to the international exchange of goods. However, the insights gained can be transferred to other types of transactions, such as international finance transactions, direct investment, and investment agreements.
Keywords: F15; K33; F02; 330; conflict of law; international private law; transaction costs; enforcement of judgements; private ordering